Correlation of mesogenic properties with intermolecular interaction energy for homologous series of HnCBP. (24th July 2017) - Srivastav, Rakesh Kumar; Roychoudhury, Mihir; Kumar, Jitendra; Kumar, Devesh
ABSTRACT: Intermolecular interaction energy between a pair of molecules of homologous series 4, 4′-disubstituted biphenyl of the general formula HO‒(CH2 )n ‒O‒C6 H4 ‒C6 H4 ‒CN(n = 3 − 11) (Hn CBP) has been evaluated under various interacting conditions viz. stacking, in-plane and terminal interaction. Molecular geometry of the studied molecules was fully optimized without any constraint and checked for imaginary frequencies using hybrid density functional B3LYP combined with 6–31 g * * basis set. Electronic structure of the molecules obtained through these calculations has been utilized to calculate electrostatic and polarization energies under Rayleigh-Schrodinger perturbation theory modified with multi-centered multi-pole expansion method. Dispersion and repulsion energies have been evaluated using Kitaigorodskii formula. The identified minimum energy complexes have been further utilized to evaluate interaction energy under super molecular approach by employing M06 and DFT-D methods. A comparative analysis of the results has been reported with a view to examine suitability of different methods to study molecular aggregations in moderately large organic systems.